2019
DOI: 10.1177/2158244019863563
|View full text |Cite
|
Sign up to set email alerts
|

Examining Patterns of Air Quality Perception: A Cluster Analysis for Southern Chilean Cities

Abstract: Various medium-sized cities in southern Chile are saturated by air pollution caused by woodsmoke. In this study, we developed a segmentation model to assess the public’s perceptions, understanding of health risks and emotional responses to poor air quality. To date, this is the first segmentation model dealing with public perception in cities contaminated by woodsmoke. A survey ( N = 489) was conducted in Temuco and Padre las Casas, Chile, which included questions regarding attitudes, sociodemographic factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…The first test reveals the significant differences between the defined groups by comparing the medians of the SO 2 concentration (Chávez, 2020 ). The second test was used post hoc to compare the pairing of each group, where a Bonferroni adjustment was necessary to increase the level of significance required (Boso et al, 2019 ; Dinno, 2015 ). The analyses of both tests were carried out with the kruskal.test and pairwise.wilcox.test functions of the statistical software R version 4.0.3, respectively (R Core Team, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The first test reveals the significant differences between the defined groups by comparing the medians of the SO 2 concentration (Chávez, 2020 ). The second test was used post hoc to compare the pairing of each group, where a Bonferroni adjustment was necessary to increase the level of significance required (Boso et al, 2019 ; Dinno, 2015 ). The analyses of both tests were carried out with the kruskal.test and pairwise.wilcox.test functions of the statistical software R version 4.0.3, respectively (R Core Team, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, some studies found no difference between how genders perceived air pollution. Low levels of education and socio-economic status may reduce the ability to perceive hazards (Boso et al 2019). People with no schooling perceived the mining impacts on the environment to be very less (Macêdo Coelho et al 2022).…”
Section: Insights From Indicator Studiesmentioning
confidence: 99%
“…For instance, studies have shown that concern about pollution tends to be higher among women [33][34][35]. Age seems to be associated with air pollution perception in a non-consistent way [36][37][38][39]. Kim, Hi, and Kim [40] have discovered higher levels of air pollution perception among young people.…”
Section: Literaturementioning
confidence: 99%
“…Forsberg, Stjernberg, and Wall [41] and Williams and McCrae [42] have indicated that middle-aged people are more sensitive to air pollution risks. A recent study in southern Chile showed that older adult women perceive the health risk of woodsmoke as less severe [39]. Several studies have found that individuals with higher levels of income and education tend to be more concerned about the impacts of air pollution on their health and largely tend to support mitigation policies [43][44][45].…”
Section: Literaturementioning
confidence: 99%